An Analysis toward Students Literary Translation of a Poetry Dreams - Fitrina Harmaini; Hanny Nabila Gusfa (Journal of Social Science, 2023)
The objective of this research was to describe the ability of third- year students to translate a poetry titled "Dreams" from English into Indonesian. The population of this study was the 3rd year English Education Department students at Universitas Bung Hatta, and the total sampling technique was used. The sample size was 26 students. The test's reliability index was 0.79 (high correlation), indicating that it was reliable. In general, the findings of this study revealed that second-year students had excellent ability in translating a poem. In general, 26 students got perfect scores (100%). The study's findings revealed that students' ability to use lexical equivalence in translating the poem was excellent. It was demonstrated by the fact that 19 students (73%), and 7 students (27%), received excellent ability. The students' ability to use grammatical adjustments in translating the poem was outstanding. It was demonstrated by the fact that 24 students scored excellent (92%), and 2 scored good (8%). Based on the findings of this study, it is possible to conclude that the second-year students' ability to translate a poem titled "Dreams" from English into Indonesian at Bung Hatta University's English Department was good.